The impact of nitrifying probiotic to population growth of pathogenic bacteria, Vibrio sp., and toxic nitrogen gasses in marine shrimp culture media under laboratory condition - Widigdo, Bambang; Yuhana, Munti; Iswantari, Aliati; Madonsa, Claritha; Sapitri, Inka Destiana; Wardiatno, Yusli; Hakim, Agus Alim; Nazar, Fitriana (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2021)
Intensification of shrimp farming has led to problems of water quality and development of pathogenic bacteria. The excess feed and fecal deposited in the bottom of the pond undergo ammonification and result in excess of ammonia formation in pond water and sediment. The purposes of this research was to investigate the impact nitrifying bacteria application on the controlling of pathogenic Vibrio sp. bacteria and toxic nitrogen gasses. Twelve (12) transparent glass bottles (effective volume of 3 L) were used in this research. Tested probiotic was purchased in free market and producer claims to contain Nitrosomonas sp., Nitrosococcus sp., Nitrobacter sp., Bacillus sp., Aerobacter sp., and Pseudomonas sp. The tested media was sea water containing Vibrio sp., TAN, NO2 and NO3 of 54.07 ± 2.93 mg/L; 6.33 ± 0.17 mg/L; 2.43 ± 0.04 mg/L; and 0.46 ± 0.01 mg/L respectively. The treatment of probiotic was 0 mg/L as a control; 0.1 mg/L; 0.2 mg/L; and 0.4 mg/L with 3 replications. In regard to concentration of Vibrio sp., NH3 and NO2 gasses, treatment doses of 0.1 mg/L (A) resulted a save level within 4 days after treatment, but to more secure in the practical work for shrimp farm, the doses of 0.2 mg/L (B) is suggested.